Evaluation of Biological Activities of Opuntia Ficus Indica Cladodes Extract Against Cadmium-Induced Osteoporosis in Male Wistar Rats - Taleb, Jihen; Ncibi, Saida; Smida, Amani; Mabrouki, Lamia; Zourgui, Lazhar (Journal of Advanced Pharmaceutical Science And Technology, 2020)
The cactus Opuntia ficus indica (L.) Mill. (Cactaceae) is widely used in Tunisian medicine for the treatment of various illnesses. The purpose of the present study was to investigate the antioxidant activities of cactus cladode extract (CCE) and to assess the protective effects of Opuntia ficus indica against osteoporosis induced by cadmium chloride in male Wistar rats. Adult male rats were divided into 4 groups of 9 each: a control group, a group injected with cadmium (3.5mg/kg) for 10 weeks, a group orally given a O. ficus indica cladodes aqueous extract (CCE) (100 mg /kg/day) for 10 weeks then treated with cadmium, and a group receiving only (CCE) for 10 weeks. Bone toxicity was estimated by examining femoral length and weight, calcium, phosphorus, alkaline phosphatase (ALP) and total tartrate-resistant acid phosphatase (ACP) levels in serum. Also, bone levels of calcium, phosphorus and vitamin C and bone mineral density (BMD) of femur diaphysis were measured. Alterations of these bone biomarkers and decreased BMD conﬁrmed cadmium-induced bone toxicity. However, when cadmium was administered in rats given CCE, all the biological parameters underwent much less alteration. Administration of CCE was found to be beneﬁcial by attenuating cadmium-induced femur damage. The protective effect of the plant is mainly attributed to its phenolic compounds that orchestrate antioxidant properties, as highlighted by HPLC-based analysis.
Keywords: Cadmium; Opuntia ficus indica (L.) Mill; Osteoporosis; HPLC analysis; Calcium and phosphorus; Bone mineral density